AN ANALYSIS OF DIRECTED DIALOGUE JOURNAL TO IMPROVE WRITING SKILL ON NEWS ITEMS TEXTS FOR INDONESIAN EFL UNIVERSITY STUDENTS - Mohammad Fatoni (Jurnal Pendidikan Edutama, 2019)
Abstract: This study aims to analyze the directed dialogue journal on news items texts for Indonesian EFL University Students in term of (1) the students’ problems in using directed dialogue journal (2) how the students’ writing after using directed dialogue journal. This research used classroom action research method. Analysis of the problems in using directed dialogue journal on news item texts was analyzed descriptively and the university students’ news items writings were analyzed in all components of writing. Results of the analysis reveals that the problems in using directed dialogue journals were lack of time and idea to response the comments. However, the lecturer were able to overcome those problems by planning what he did in the lesson plan efficiently and training how to response the comments in the written conversation to improve their writing. In successions overall, there was significant improvement on the students class mastery of final draft from the first to third cycles. They were 38.5%, 65%, 92%. Content was the writing component that improves significantly in this research. It means that directed dialogue journal on news items texts was able to improve the students writing skill when the problems were identified and solved. Keywords: directed dialogue journal, news items texts, writing components Abstrak: Penelitian ini bertujuan untuk menganalisis dialog jurnal terarah pada penulisan teks berita yang ditujukan untuk mahasiswa Indonesia yang menggunakan bahasa inggris sebagai bahasa asing dalam hal (1) permasalahan yang mahasiswa hadapi dalam menggunakan dialog jurnal terarah dan (2) bagaimana tulisan mahasiswa setelah menggunakan dialog jurnal terarah. Penelitian ini menggunakan metode penelitian tindakan kelas. Masalah dalam menerapkan dialog jurnal terarah pada teks berita berita dianalisis secara deskriptif dan semua komponen teks tulis berita mahasiswa dianalisis. Hasil analisis mengungkapkan bahwa masalah dalam melaksanakan dialog jurnal terarah adalah kurangnya waktu dan ide untuk merespon komentar yang diberikan. Namun, dosen mampu mengatasi masalah tersebut dengan merencanakan apa yang dia lakukan dalam rencana pengajaran secara efisien dan melatih bagaimana merespon komentar dalam percakapan tertulis untuk meningkatkan tulisan mereka. Secara berturut-turut, ada peningkatan yang signifikan pada penguasaan kemampuan menulis pada draf akhir dari siklus pertama hingga ketiga sebesar 38,5%, 65%, 92%. Isi merupakan komponen tulisan yang meningkat secara signifikan dalam penelitian ini. Hal ini menunjukkan pengunaan dialog jurnal terarah pada materi teks berita dapat meningkatkan keterampilan menulis mahasiswa ketika permasalahannya diidentifikasi dan dipecahkan. Kata kunci: dialog jurnal terarah, teks berita, komponen tulisan.